Upregulation of long non-coding RNA RAB1A-2 induces FGF1 expression worsening lung cancer prognosis. (1st December 2018) - Wu, Di; Yang, Binyao; Chen, Jiansong; Xiong, Huali; Li, Yinyan; Pan, Zihua; Cao, Yi; Chen, Jinbin; Li, Tiegang; Zhou, Shiyu; Ling, Xiaoxuan; Wei, Yongfang; et al.
Abstract: The chromosomal locations of lncRNAs (long non-coding RNAs, lncRNAs) infer their biological functions in cancer. Lnc-RAB1A-2, a Ras-related protein Rab-1A (RAB1A) upstream lncRNA, was chosen for assessment of its impact on lung cancer prognosis in a case-based analysis and investigation of its biological function though a series of functional assays. Lnc-RAB1A-2 was significantly upregulated in 276 lung cancer tissues compared with corresponding non-tumor tissues, and its expression level was significantly correlated with clinical stage and metastasis status in lung cancer patients. Patients with high expression levels of this lncRNA had a shorter median survival time (16.0 months vs. 23.0 months, P  = 0.011 in southern samples; 8.0 months vs. 19.0 months, P  = 0.020 in eastern samples; 13.0 months vs. 19.0 months, P  = 0.002 in merged samples) and a higher risk of death than those with lower levels (HR = 1.52; 95% CI = 1.01–2.26, in merged samples). Additionally, overexpression of lnc-RAB1A-2 significantly promoted lung cancer cell proliferation in vitro and in vivo . Further analyses using digital gene expression tag profiling revealed that lnc-RAB1A-2 could affect the expression of fibroblast growth factor 1 (FGF1), a gene involved in the PI3K/AKT/mTOR pathway that is largely activated by RAB1A. FGF1 was confirmed to be a down-stream gene of lnc-RAB1A-2 . Collectively, our study demonstrated that lnc-RAB1A-2 is associated with poor lung cancer prognosis by promoting lung cancer development. Highlights: Lnc- RAB1A-2 is associated with tumorigenesis, progression, and metastasis. Lnc- RAB1A-2 may serve as a prognostic factor in lung cancer. Lnc- RAB1A-2 significantly influenced tumor growth and metastasis both in vivo and in vitro.